2020
DOI: 10.1002/bse.2633
|View full text |Cite
|
Sign up to set email alerts
|

How to respond to competitors' green success for improving performance: The moderating role of organizational ambidexterity

Abstract: With increasing environmental competitions between companies, there is a pressing need to explore how the environmental pressures from rivals influence focal firms' actions and the subsequent performance consequences. On the basis of social contagion theory and upper echelons theory, we examine whether firms respond to competitors' green success through green supplier integration, which further improves firm performance, and the moderating effect of organizational ambidexterity. The research explores hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 93 publications
(154 reference statements)
4
35
1
Order By: Relevance
“…In turn, this makes it difficult for firms to select the appropriate action about whether and when to adopt. In this situation, imitating the behavior of other firms within the supply chain network provides a low‐cost solution to that uncertainty (McFarland et al, 2008; Zhao et al, 2020). Moreover, when firms work jointly to resolve environmental challenges, they also influence each other's expectations and beliefs, enabling the contagion of green practices across supply chains (Mena & Schoenherr, 2020).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this makes it difficult for firms to select the appropriate action about whether and when to adopt. In this situation, imitating the behavior of other firms within the supply chain network provides a low‐cost solution to that uncertainty (McFarland et al, 2008; Zhao et al, 2020). Moreover, when firms work jointly to resolve environmental challenges, they also influence each other's expectations and beliefs, enabling the contagion of green practices across supply chains (Mena & Schoenherr, 2020).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…The high levels of interactions help to improve information sharing and collective actions across organizations (Rapp et al, 2013). Besides, close contacts help manufacturers and suppliers to resolve uncertainty through the sharing of green success, which would mitigate the risks of implementation (Angst et al, 2010; Zhao et al, 2020). Therefore, close interaction triggers the cohesive mechanism of supply chain contagion (Li et al, 2018).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Previous research has indicated that BD is beneficial to organizational performance and competitive advantage. 33 , 34 , 36 , 37 We believe that BD is a better strategy to understand how ambidexterity works in the organizational change process.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…The second conclusion is that organizational green learning plays a partially mediating role in the relationship between green innovation strategy and green innovation performance. Managers should concentrate on the latest green-related knowledge and information inside and outside the organization, and even the green success of competitors [65], in order to improve the performance of incremental innovation in times of technological turbulence. Enterprises can also establish platforms (such as inter-enterprise social media) for external and internal stakeholders to communicate and cooperate with each other by sharing green knowledge and information.…”
Section: Discussionmentioning
confidence: 99%